Long-lasting and Sex-dependent Effects of Postweaning Swimming Exercise on Social Dominance in Adult Mice. (21st August 2022) - Song, Li; Mao, Jiawen; Wang, Qian; Chen, Aixin; Sun, Ruoxuan; Li, Xuzi; Luo, Jiaqi; Zhao, Penghui; Shi, Yun; Su, Yanju; Liu, Keyao; Yuan, Fang; et al.
Highlights: Postweaning swimming exercise improved social dominance in mice. Postweaning swimming exercise had long-lasting and sex-dependent effects on enhancing social dominance in mice. Metabolomics analysis was conducted to explore the underlying mechanism. Abstract: Increasing evidence has shown that early life events exert long-lasting effects on brain function and mental diseases. Exercise has been proven to have many positive effects on behaviors, such as reducing anxiety- and depression-like behaviors and alleviating cognitive impairment. However, the long-lasting and even short-term effects of regular swimming exercise on social dominance remain unclear. The purpose of this study was to investigate the potential effects of postweaning swimming exercise on social dominance and metabolic adaptation in adult mice. Three-week-old mice performed 1 h of swimming exercise in warm water for 4 weeks. A series of behavioral tests, such as the social dominance test (SDT), open field test (OFT), and forced swim test (FST), were conducted. Behavioral test results showed that both male and female mice in the swimming group had a higher rank than those in the sedentary group in the SDT of early adulthood, while only female mice in the swimming group maintained the social dominance in late adulthood. There was no difference between the swimming and sedentary groups in anxiety- and depression-like behaviors. Metabolomics analysis showed that there were alterations in particular metabolites and signaling pathways after one month of swimming exercise, including sphingolipid metabolism, neuroactive ligand–receptor interaction and caffeine metabolism. In conclusion, our results provide the first evidence that postweaning swimming exercise has long-lasting and sex-dependent effects on social dominance, which may be caused by metabolic adaptation.